PDC CORPORATE REBRANDING PROCESS TO BE CUSTOMBANDUNG - Chan, Arianis; Eunike, Febe (Jurnal Manajemen Bisnis, 2019)
The purposes of this research are to determine the stages of the corporate rebranding process of PDC to Custombandung. PDC is a custom merchandise business that provides various types of products that can be customized by consumers. The method used was descriptive qualitative. The techniques of collecting data used were the interview, observation, and literature study. According to the result of this research, Custombandung had done the corporate rebranding process well. First, the repositioning stage was done with changing the brand identity and expanding the market. Second, the renaming stage was done with changing the name from PDC to Custombandung. Third, the redesign stage was done by changing the visual elements, which were a logo, website, and social media appearance and packaging. Fourth, the relaunch stage was done for the internal stakeholders and the external stakeholders. This research concludes that the corporate rebranding process by Custombandung has been done well.